Deletion of the RNLS Gene using CRISPR/Cas9 as Pancreatic Cell β Protection against Autoimmune and ER Stress for Type 1 Diabetes Mellitus - Baraja, Aufa; Sunarto , Fadhilla Rachmawati; Adji, Arga Setyo; Handajani , Fitri; Rahman, Firman Suryadi (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Type 1 diabetes mellitus (T1DM) is a chronic disease in children which is usually caused by autoimmunity that damages pancreatic a and b cells which have functions as blood glucose regulators. Some studies stated that Renalase (RNLS) gene deletion will protect these b cells from autoimmune reactions and Endoplasmic Reticulum (ER) stress. RNLS deletion by genome editing Clustered Regular interspersed Short Palindromic Repeats-CRISPR-related (CRISPR/Cas9) is believed to have the potential to be a therapy for T1DM Patients. AIM: This research was conducted to know the potential of RNLS deletion using the CRISPR/Cas9 as an effective therapy and whether it has a permanent effect on T1DM patients. METHODS: The method applied in this research summarized articles by analyzing the titles and abstracts of various predetermined keywords. In this case, the author chose a full-text article published within the past 10 years by prioritizing searches in the last 5 years through PubMed, Google Scholar, Science Direct, Cochrane, American Diabetes Association, and official guidelines from IDAI. RESULTS: RNLS deletion using CRISPR/Cas9 in mice weakened the response of polyclonal -cell-reactive CD8+ T cells and disrupted the immune recognition to cells so that autoimmune killing did occur. In addition, such deletion prevents RNLS ER stress by increasing the threshold, triggering the unfolded protein response so that ER stress is difficult to occur. RNLS mutations in b cells also increase b cell survivability to oxidative stress. CONCLUSION: b cells RNLS deletion by genome editing CRISPR/Cas9 is effective in protecting b cells from autoimmune reactions and RE stress. However, further research is needed to determine the side effects and safety of its use.